The KNOW-CKD Study: What we have learned about chronic kidney diseases - Kook-Hwan Oh; Minjung Kang; Eunjeong Kang; Hyunjin Ryu; Seung Hyeok Han; Tae-Hyun Yoo; Soo Wan Kim; Dong-Wan Chae; Kyu-Beck Lee; Sue K. Park; Yeong Hoon Kim; Curie Ahn; et al. (The Korean Society of Nephrology, 2020)
As the nation's largest chronic kidney disease (CKD) cohort, the KoreaN Cohort Study for Outcomes in Patients With Chronic Kidney Disease (KNOW-CKD) was established to investigate the clinical course, risk factors for progression, and adverse outcomes of CKD. From 2011 to 2016, the KNOW-CKD recruited 2,238 adult patients with CKD from stage G1 to G5 who were not receiving renal replacement therapy from nine tertiary care hospitals throughout Korea. As of 2019, the KNOW-CKD has published more than 50 articles in the areas of socio-economics, nutrition, quality of life, health-related habits, CKD progression, cardiovascular comorbidity and outcome, anemia, mineral bone disease, biomarker discovery, and international and inter-ethnic comparisons. The KNOW-CKD will eventually offer a prediction model for long-term consequences of CKD, such as the occurrences of end-stage renal disease, cardiovascular disease, and death, thereby enabling the identification and treatment of at-risk populations that require extra medical attention.